The Role of Spiritual Unit (Chaplaincy) in The Development of Islamization of Health Management in Al-Islam Specialist Hospital, Kuala Lumpur - Mohamad Shafi, Surina; Awang, Mohd Zulkifli; Mas’ud, Ishak; Amir Ramli, Nurul Aisyah (‘Abqari Journal, 2023)
This paper discussed the role of the Spiritual Unit (Chaplaincy) of Al-Islam Specialist Hospital to implement the process of Islamization of health management in the administration. The study will unravel the history and the role of Spiritual Unit (Chaplaincy) on the development of hospital staff as well as the contribution to other health sectors. This research is using qualitative research methods where the research is founded on a comprehensive study of current literature on Muslim chaplaincy and Islamization in healthcare management. Important reviews of these literature studies have resulted in the study that found the role of the Spiritual Unit (Chaplaincy), Al-Islam Specialist Hospital has successfully strengthened the hospital management journey in implementing da’wah bil hal through the concept of Ibadah Friendly Hospital (IFH) and successfully left an impact on health management through the Islamization process that has been implemented. Thus, the Spiritual Unit (Chaplaincy) plays a significant role in transforming the paradigm of health management in a complete and holistic way, in addition to its major role in offering spiritual care to patients.